Photonuclear method of production Cu-67 - Aizatskyi, N.I.; Dikiy, N.P.; Dovbnya, A.N.; Dolzhek, M.A.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V. (Вопросы атомной науки и техники, 2014)
The efficiently separation of ⁶⁷Cu is achieved by using diantipyrylpropylmethane (DАPPМ). Experimental separation of ⁶⁷Cu from sulphuric solution (1 mol./L) of zinc (2 mol./L) with addition potassium iodide (0.1 mol./L) is realized with help DAPPM (0.02 mol./L), which dissolve in chloroform. The 84.4% ⁶⁷Сu was extracted from water phase of ZnSO₄ into organic phase (solution DAPPM in chloroform). The ⁶⁷Cu remainder in organic phase is 4.6%. Effective extraction of protonated forms of reagent and ionic associate of metal+halide was realized by means of antipyrin forms in acid halide solution. The decrease of acidity of a water phase is necessary for effective reextraction. Re-extraction was realised by means of consecutive washing of organic phase (DAPPM in chloroform) by means of distilled water. Some amount of ZnSO₄ in process of extraction gets in organic phase that causes a low level re-extraction in first two tests. These tests re-extraction have low values рН. Re-extraction ⁶⁷Cu from solution DAPPM in chloroform is carried out consistently four times by distilled water. The activity of ⁶⁷Cu in third and fourth re-extraction tests was 72.7%.